2018
DOI: 10.15171/npj.2018.31
|View full text |Cite
|
Sign up to set email alerts
|

Role of erythropoietin in methotrexate-induced nephrotoxicity in adult male albino rats

Abstract: Introduction: Methotrexate (MTX) could provoke a renal dysfunction. However, beneficial extra-hematopoietic effect of erythropoietin might guard against MTX-induced nephrotoxicity. Objectives: Determination of renoprotective erythropoietin’s role against MTX-induced nephrotoxicity through elucidating its renofunctional and renomorphological effects in adult male albino rats. Materials and Methods: The study was performed on 60 adult male Albino rats, equally divided into three groups; group 1 (control): tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…This is similar to the findings of other previous studies. 7,8 The exact mechanism of MTX nephrotoxicity was unclear. However, some studies found that the main factor in MTXrelated tissue injury was oxidative damage, with successive generation of more free radicals, the role of oxidative stress has been reported in MTX-induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is similar to the findings of other previous studies. 7,8 The exact mechanism of MTX nephrotoxicity was unclear. However, some studies found that the main factor in MTXrelated tissue injury was oxidative damage, with successive generation of more free radicals, the role of oxidative stress has been reported in MTX-induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…6 Histologically in MTX-treated rats, kidneys showed: enlargement of Bowman capsule cavity, infiltration of lymphocytes, diminish of glomeruli size, an increase in blood cells count and degeneration of tubules. 7,8 Like other drugs with nephrotoxic effects, MTX-induced renal function declination is clinically tested by observation of hematuria and deterioration in serum urea and creatinine level. Reproduction of such effects is done in research studies in animals after a single dose of MTX.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapeutic drugs are broadly used against various kinds of cancer and their clinical use is associated with the occurrence of unfavorable side effects including many organ toxicities [1]. One of these drugs is methotrexate (MTX) which is a folate antagonist used to treat oncologic and non-oncologic conditions like psoriasis and rheumatoid [2].…”
Section: Introductionmentioning
confidence: 99%
“…Renal impairment developed by the use of MTX was characterized laboratorially by the abrupt rise of serum creatinine and urea with marked elevation of plasma MTX concentration and characterized pathologically by structural changes as degeneration and dilation of renal tubules and glomeruli degeneration [1]. Moreover, the pathogenesis of MTX-induced toxicity involved oxidative stress which played a crucial task in triggering inflammation and apoptosis processes [2,4,5,6].…”
Section: Introductionmentioning
confidence: 99%